2021
DOI: 10.1038/s41598-021-94364-5
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal plus subcutaneous prime vaccination with a dual antigen COVID-19 vaccine elicits T-cell and antibody responses in mice

Abstract: We have developed a COVID-19 vaccine, hAd5 S-Fusion + N-ETSD, that expresses SARS-CoV-2 spike (S) and nucleocapsid (N) proteins with modifications to increase immune responses delivered using a human adenovirus serotype 5 (hAd5) platform. Here, we demonstrate subcutaneous (SC) prime and SC boost vaccination of CD-1 mice with this dual-antigen vaccine elicits T-helper cell 1 (Th1) biased T-cell and humoral responses to both S and N that are greater than those seen with hAd5 S wild type delivering only unmodifie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 60 publications
1
21
0
Order By: Relevance
“…Recently, a study showed that express wild-type or modified S protein by Ad5 via neither s.c. nor i.n. immunization was able to detect the IL-4 + T cell response [46] . However, our studies showed that AdCoV2s elicited strong antibody response (e.g., AdCoV2-S; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study showed that express wild-type or modified S protein by Ad5 via neither s.c. nor i.n. immunization was able to detect the IL-4 + T cell response [46] . However, our studies showed that AdCoV2s elicited strong antibody response (e.g., AdCoV2-S; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…COH04S1 and MVA-SARS-2-S, an MVA vector expressing S alone, are currently the only MVA-based SARS-CoV-2 vaccines that are clinically evaluated 61 . In addition, COH04S1 and a recently developed adenovirus vector approach are currently the only clinically evaluated SARS-CoV-2 vaccines that utilize an antigen combination composed of S and N 62 . These findings highlight the potential importance of COH04S1 as a second generation multiantigenic SARS-CoV-2 vaccine to contribute to the establishment of longterm protective immunity to prevent COVID-19 disease.…”
Section: Discussionmentioning
confidence: 99%
“… Type Vaccine Target Route (no. of doses) Animal used Ad-vectored vaccine ChAd-SARS-CoV-2-S S protein IN (1) hACE2 mice 33 , 43 and rhesus macaques 42 ChAd-SARS-CoV-2-S S protein IM or IN, (1) Golden Syrian hamsters 35 AdCOVID RBD protein IN (1) Mice 44 Ad5.SARS-CoV2-S1 S1 protein IN or SC, (1) Mice 45 ChAdOx1 S protein IM or IN, (1 or 2) Ferrets 47 , hamsters and rhesus macaques 46 Ad5-nCoV Full-length S protein IM or IN, (1); or oral + IN, simultaneously, (1) Mice and ferrets 38 Ad5-S-nb2 S protein IM or IN, (1) Mice and rhesus macaques 39 Ad5‐N N protein IN (2) Mice 52 AdC7-S, AdC7-RBD and AdC7-RBD-tr2 S, RBD or tandem-repeat dimeric RBD IM or IN, (2) hACE2 mice 50 S and N proteins SC or IN, (1) Mice 51 Lentivirus-vectored vaccine S protein IP + IN (2); or IM + IN (2) Mice and golden hamsters 57 S protein IM + IN, (2) hACE2 mice 58 Influenza virus-vectored vaccine ∆NA(RBD)-Flu virus RBD pro...…”
Section: Recent Progress In the Development Of Intranasal Covid-19 Vaccinesmentioning
confidence: 99%
“… 50 N protein alone, or combined with S protein, can also be the target of Ad vector-based IN vaccines, which could induce strong N- and S-specific immune responses in mice. 51 , 52 Further studies are necessary to strengthen the potential of N protein as an ideal vaccine target for SARS-CoV-2.…”
Section: Recent Progress In the Development Of Intranasal Covid-19 Vaccinesmentioning
confidence: 99%